Maternal fetal outcomes of pregnancy complications with ovarian cancer (Research, Society and Development, 2021)
Ovarian cancer remains the deadliest type of gynecology malignancy in the United States. while there are several histological subtypes of ovarian cancer, epithelial cell types are the most common variant and therefore contribute most to the morbidity and mortality attributed to ovarian malignancy. Therefore, we performed a systematic review of the literature to delineate the characteristics and outcomes of EOC during pregnancy. This review was conducted based on the MOOSE guideline for systematic reviews using public search engines PubMed and MEDLINE. The input keywords used for the search were ''pregnancy'' and ''ovarian cancer''. The search was limited to articles published in English between January 1955 and November 2013. The main conclusions of our review of the literature are that mothers outcomes of pregnancy complicated by EOC are highly contingent on the stage of diagnosis and histological type. The majority of expectantly managed pregnancies resulted in successful neonatal outcomes. Serious adverse events during pregnancy were less frequent than observed in other histological types of ovarian tumor.